SCREENING OF SOIL BACTERIA FOR PLANT GROWTH PROMOTION ACTIVITIES IN VITRO - Edi Husen (Indonesian Agency for Agricultural Research and Development, 2003)
Fourteen isolates of soil bacteria, including two known plant growth promoting rhizobacteria (PGPR) strains, Azotobacter vinelandii Mac 259 and Bacillus cereus UW 85, were tested in vitro. Parameters assessed were indoleacetic acid (IAA) production, phosphate solubilization, dinitrogen fixation, and siderophore (Fe-III chelating agent) production. IAA production was assayed colorimetrically using ferric chlorideperchloric acid reagent. Phosphate-solubilization and siderophore production were tested qualitatively by plating the bacteria in Pikovskaya and chrome azurol S agar, respectively. The ability to fix dinitrogen was measured based on nitrogenase activity of the bacteria by gas chromatography. The results showed that twelve isolates produced IAA, ranged from 2.09 to 33.28 µmol ml-1. The ability to solubilize precipitated phosphate was positively exhibited by four isolates (BS 58, BTS, TCaR 61, and BTCaRe 65). Seven isolates including Mac 259 positively produced siderophore. None of the isolates showed nitrogenase activity. Only one isolate (TS 3) did not exhibit any of the traits tested. Isolate TCeRe 60 and reference strain Mac 259 were found to have IAA- and siderophore-producing traits. Four P-solubilizing bacteria (BS 58, BTS, TCaR 61, and BTCaRe 65) were also IAA- and siderophore-producing bacteria. Potential use of these PGPR isolates needs further test in enhancing plant growth.